An Interference Avoidance Method of Wireless Body Area Network Based on Chinese Medical Band - Weixia Zou; Chao Guo; Fengyuan Kang; Chunqing Zhang (International Journal of Distributed Sensor Networks)
An interference avoidance mechanism for Chinese Wireless Body Area Network (WBAN) is proposed in this paper. This mechanism firstly classifies the channels by priority based on the distribution characteristics of potential interference on the China medical band, commits energy detection on all channels in the network initialization phase, and compares to energy threshold to form available channel set. Then differentiated channel maintenance strategy is utilized to avoid interference as far as possible in network running phase. The scheme proposed in this thesis is proved to be superior by simulation from either the interference probability or packet loss rate. Apart from that, the interference detection threshold that can satisfy the least communication demand is calculated for every Type B, C channel by simulation and convenient for referring to.